2010
DOI: 10.4028/www.scientific.net/msf.638-642.1215
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Measurements of Thermal Residual Stresses in AA2024-T3 Friction Stir Welds as a Function of Welding Parameters

Abstract: Prediction and measurements of thermal residual stresses in AA2024-T3 friction stir welds as a function of welding parameters Dubourg, L.; Doran, P.; Larose, S.; Gharghouri, M. A.; Jahazi, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In their research, prior to welding, the samples were mechanically loaded to about 70% of the tensile yield strength in an in situ loading apparatus and it is observed that the imposed mechanical loading leads to large compressive residual stresses after welding. Dubourg et al [6] have investigated the effect of welding parameters on thermal residual stress in friction stir welding of AA2024 using a three-dimensional model. Yujie et al [7] have studied the residual stress distribution and effect of postweld cold rolling process on residual stress of friction stir welded aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, prior to welding, the samples were mechanically loaded to about 70% of the tensile yield strength in an in situ loading apparatus and it is observed that the imposed mechanical loading leads to large compressive residual stresses after welding. Dubourg et al [6] have investigated the effect of welding parameters on thermal residual stress in friction stir welding of AA2024 using a three-dimensional model. Yujie et al [7] have studied the residual stress distribution and effect of postweld cold rolling process on residual stress of friction stir welded aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of strain gauge measurements however, the cross point from tensile to compressive stress is at a position of about 20 mm, different than that of the calculation and laser ultrasonics. Recent results from the neutron diffraction technique showed that the cross point is closer to that of laser ultrasonics [23]. …”
Section: Figure 14 Near Herementioning
confidence: 99%
“…The thermal cycles are used to predict residual stresses [6][7][8] or metallurgical features such as the precipitation state in the material [9,10]. They can be computed analytically by using Rosenthal's equation [11] for a moving single-point heat source, or numerically by using the finite difference method or the finite element method (FEM).…”
Section: Introductionmentioning
confidence: 99%